Relative clauses in Uto-Aztecan Languages from the Sierra Tarahumara: an Intra-genetic Panorama with Particular Attention to Yaqui - Estrada, Zarina (2020)
This paper makes a typological contribution by describing relative clauses in Uto-Aztecan languages spoken, by centuries, in a geographical area of northwestern Mexico, known as the Sierra Tarahumara (Pima Bajo, Northern Tepehuan, Tarahumara and Guarijío, although for comparative purposes Yaqui is also considered). Relative clauses observed in these languages show that they are nominalized or non-nominalized. Comparative evidences available for the analysis reveals that the relativizers or subordinators observed in at least three of the languages come from demonstrative elements, and that genitive subjects, one of the main properties of clausal nominalizations are disappearing in two of the languages. This fact implies a diachronic change to finite constructions.